Women prisoners in the criminal justice system : towards equal treatment and recognition of difference : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts (Social Policy), Massey University - Agnew, Margaret B. M (Massey University, 2001)
This thesis is about the extent to which women who have received custodial sentences have their criminogenic needs met: that is how they are assisted to lead good lives without further offending. I approached the thesis from the perspective that women who have been imprisoned are entitled to be treated equally with men: to be imprisoned for the same seriousness of offences. They should have the same benefits, such as contact with families. They should at least receive the same level and quality of preparation for life after prison and equal standards of accommodation. In addition the genuine social differences between men and women should be recognized. Women are usually the main caregivers for children. Typical women prisoners are also solo parents, and so have the financial responsibility for of financial support for children as well as care. However, most of the women have few qualifications or opportunities for making a living to support their families that does not involve law-breaking. A recognition of these differences should lead to some supports being provided to women prisoners, such as education and training. In my interviews with women ex-prisoners and prison managers, and in surveying the literature I found that neither women's rights to equal treatment nor their differences were adequately reecognised in past or present penal policy. Whilst it is true that the minority status of the female prison population poses challenges for policy, it does not explain the systematic disadvantage faced by women in prison. There are alternative policies which could very well be more appropriate and some of these are set out in the concluding chapter to the thesis.
Keywords: New Zealand; Women prisoners; Reformatories for women